Diary in America, Series One - Marryat, Frederick, 1792-1848 (Salt Lake City, UT : Project Gutenberg, 2007)
"Diary in America, Series One" by Captain Frederick Marryat is a travel narrative written in the mid-19th century. The book presents the author's keen observations during his travels through the United States and Canada, dissecting the cultural and societal differences he encounters in a rapidly changing America. Marryat embarks on a journey to explore the complexities of American society, assessing the impacts of democracy and various state identities on the collective character of its people. The opening of this work establishes Marryat's intent to provide an insightful critique of American society and its institutions, shaped by his extensive travel and prior literary experience. He reflects on the stark contrasts he observes in New York City, describing it initially as reminiscent of a provincial English town, before coming to appreciate the nuances it holds. The narrative also touches on the state of transition America is in, characterized by distinct regional identities amidst the burgeoning democratic spirit. Through his anecdotes and observations, Marryat sets the stage for a detailed examination of the American character against the backdrop of its political and social evolution. (This is an automatically generated summary.)
Release date is 2007-10-21
Produced by Nick Hodson of London, England
Keywords: United States -- Description and travel; Canada -- Description and travel; United States -- Social life and customs -- 1783-1865; Marryat, Frederick, 1792-1848 -- Travel -- America